The capacitated vehicle routing problem with alternative objective functions - Damião, Caio Marinho (2023)
[EN] The Capacitated Vehicle Routing Problem (CVRP) deals with minimizing the total distance traveled by the routes and is widely studied in the literature. Despite having many applications, such as in the distribution of consumer goods, several authors in the literature have had the perception that the classic CVRP does not apply to other cases, such as, for example, school bus routing or emergency aid distribution in case of large disasters. Therefore, variants with alternative objective functions for this problem have been proposed in the literature in order to assure satisfactory solutions in these scenarios. This dissertation studies three CVRP variants proposing a Branch-cut-and-price model for each one. The first variant discussed here is the Cumulative CVRP, where the objective is to minimize the sum of arrival times for all customers. The second variant studied in this work is the Min-Max CVRP, which aims at minimizing the distance covered by the longest route and is a well-known method of balancing routes. The third variant, CVRP with a balanced number of customers, was proposed in this work and aims to ensure a balance of routes in terms of the number of customers visited by each vehicle